Efektifitas Konseling Kelompok Teknik Cognitive Defusion Terhadap Self-Confidence Siswa Introvert - Al Ridwan, Muhammad Faisal; Galugu, Nur Saqinah; Anuar, Arman Bin (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2025)
This study aims to examine the effectiveness of group counseling services using cognitive defusion techniques in improving self-confidence among introverted students at SMAN 2 LUWU and to identify the differences in their self-confidence before and after the intervention. This quasi-experimental study used a one-group pre-test and post-test design to measure the level of self-confidence before and after the intervention. The sample was selected through purposive sampling and consisted of six students from class XI IPS 1 and XI IPS 2 who were identified as having low self-confidence. Data were collected using a self-confidence questionnaire, an interview, and observation. The results show that group counseling employing cognitive defusion techniques is effective in enhancing the self-confidence of introverted students, as demonstrated by the significant improvement in scores from the pre-test to the post-test (mean score before = 41.67; after = 94.17; improvement = 52.5). Furthermore, the paired sample T-test revealed a significance value (2-tailed) of 0.000 (p < 0.05), indicating a significant difference. Thus, the study confirms the hypothesis (H1) that group counseling with cognitive defusion techniques can significantly improve the self-confidence of introverted students. _____________________________________________________________Penelitian ini bertujuan untuk menguji keefektifan layanan konseling kelompok dengan teknik cognitive defusion dalam meningkatkan self-confidence pada siswa introvert di SMAN 2 Luwu. Latar belakang penelitian ini adalah rendahnya kepercayaan diri siswa introvert yang ditandai dengan keraguan dalam bertanya dan menjawab di kelas, ketakutan mengikuti kegiatan ekstrakurikuler, serta minimnya partisipasi sosial. Penelitian menggunakan pendekatan kuantitatif dengan desain quasi-experiment tipe one group pretest-posttest. Sampel terdiri dari enam siswa kelas XI IPS 1 dan XI IPS 2 yang dipilih melalui purposive sampling. Teknik pengumpulan data meliputi angket skala self-confidence, wawancara, dan observasi. Hasil penelitian menunjukkan bahwa layanan konseling kelompok dengan teknik cognitive defusion efektif dalam meningkatkan self-confidence. Hal ini terlihat dari peningkatan rata-rata skor self-confidence dari 41,67 pada pre-test menjadi 94,17 pada post-test, dengan kenaikan sebesar 52,5. Uji Paired Sample T-Test menunjukkan nilai signifikansi (2-tailed) sebesar 0,000 ≤ 0,05, yang berarti terdapat perbedaan signifikan antara sebelum dan sesudah perlakuan. Dengan demikian, hipotesis H1 diterima dan layanan yang diberikan terbukti efektif.